Analisis Validitas dan Reliabilitas Instrumen dalam Penelitian Bimbingan dan Konseling melalui Literature Review - Anasari Anasari; Lidiana Rahayu Ningsih; Risma Anita Puriani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the quality of assessment instruments in educational research through a literature review approach. The focus of this study includes the analysis of validity, reliability, item difficulty level, and item discrimination index as the main indicators in determining instrument quality. This research employs a literature review method by examining various relevant scientific sources published within the last five years. The findings indicate that validity plays a role in ensuring the accuracy of the instrument in measuring the intended construct, while reliability refers to the consistency of measurement results. In addition, the difficulty level provides an overview of item characteristics, and the discrimination index functions to differentiate students' abilities. These four aspects are interrelated and serve as the foundation for producing accurate and effective assessment instruments. The implications of this study suggest that comprehensive instrument testing is essential to improve the quality of educational evaluation and to support appropriate decision-making in the field of education.